Efforts to Enhance Australia's Cyber Security by Developing of a Partnership with Indonesia in the Field of Cyber Diplomacy - M Aditya Gerald (Global Local Interactions: Journal of International Relations, 2023)
This article examines the Australian government's endeavors to enhance cybersecurity by means of cyber diplomacy with Indonesia. This article utilizes qualitative descriptive methodologies. The data sources utilized encompass scholarly publications, books, research reports, and electronic media pertaining to the research topic. This article will examine the use of Australia's cyber diplomacy with Indonesia by utilizing the principles of cybersecurity and cyber diplomacy to enhance the robustness of cybersecurity. Australia engages in cyber diplomacy with Indonesia to enhance cybersecurity, based on the principle of international cooperation in this field. Australia implements a capacity building strategy, aligned with its 2017 International Cyber Engagement Strategy policy, to fortify Indonesia's cybersecurity. This endeavor will also contribute to the enhancement of Australia's own cybersecurity, given the interconnected nature of cyber threats. Australia's efforts to enhance Indonesia's capabilities are implemented through various collaborative initiatives, specifically the Cyber Policy Dialogue and Cyber Bootcamp programs. Examining this research is intriguing because to the involvement of Australia and Indonesia in cyber warfare, as well as their recent efforts to re-establish cyber-related diplomacy.